Miary zagrożenia w zarządzaniu inwestycjami - Dziawgo, Ewa (Downside Risk Measures in Investment Management, 2007)
The increase in the risk of running the business triggers the demand for new methods of risk management. The accurate risk measurement is one of the elements of risk management. There are three groups of risk measures: volatility measures, sensitivity measures, downside risk measures. The article characterizes those downside risk measures, which determine unfavourable deviation from the expected price values, or rates of return, which can be present in adverse market conditions. The article is specifically focused on VaR, as it is the measure which is a component of many models facilitating decision making process of capital allocation for executives.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 98-105